Medium supplementation with human, but not fetal calf serum facilitates endocytosis of PLGA nanoparticles by human primary B-lymphocytes via complement opsonization - Pusch, Lennart; Brox, Regine; Cunningham, Sarah; Fischer, Dagmar; Hackstein, Holger (Biochemical and Biophysical Research Communications, 2023)
The “biological identity” of nanoparticles (NPs) is governed by a shell consisting of various biomolecules that is formed upon exposure to biological media, the so-called biomolecule corona. Consequently, supplementation of cell culture media with e.g. different sera is likely to affect interactions between cells and NPs ex-vivo, especially endocytosis. We aimed to investigate the differential impact of human and fetal-bovine serum on the endocytosis of poly (lactic-co-glycolic acid) NPs by human peripheral blood mononuclear cells via flow cytometry. Furthermore, we employed different methods to inhibit endocytosis, providing mechanistic insights. The resulting biomolecule corona was characterized via denaturing gel electrophoresis. We found profound differences between human and fetal bovine serum regarding the endocytosis of fluorescently labeled PLGA nanoparticles by different classes of human leukocytes. Uptake by B-lymphocytes was particularly sensitive. We further present evidence, that these effects are mediated by a biomolecule corona. We demonstrate to our knowledge for the first time that the complement is an important contributor to the endocytosis of non-surface-engineered PLGA-nanoparticles prepared via emulsion solvent evaporation by human immune cells. Our data demonstrates that results obtained with xenogeneic culture supplements such as fetal bovine serum may have to be interpreted with caution.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Biomolecule corona; Complement; Culture medium; Nanoparticles; PLGA